Kombinasi Metode Fuzzy Multiple Attribute Decision Making (FMADM) dan Simple Additive Weighting (SAW) Untuk Menentukan Calon Reviewer Internal Universitas Islam Kuantan Singingi - Haswan, Febri; Nopriandi, Helpi (Forum Kerjasama Pendidikan Tinggi, 2021)
The Institute for Research and Community Service (LPPM) of the Islamic University of Kuantan Singingi annually selects prospective internal reviewers, in which the current selection process is carried out by looking at the requirements for prospective reviewers who register at the LPPM section, then these requirements will be selected one by one. with the provisions that have been set, the results of the assessment obtained by each candidate will be ranked based on the highest value to the lowest value, the selection process in this way is sometimes less effective and causes errors during the assessment, this can later be detrimental to the nominating participants. In this study, the author tries to apply the FMADM and SAW methods which can help LPPM in selecting prospective internal reviewers. This Fuzzy Multiple Attribute Decision Making (FMADM) method will later be used to find alternatives from a number of alternatives with certain criteria, while the Simple Additive Weighting (SAW) method is used to find the weighted summation of the performance ratings on each alternative of all attributes, the results obtained from both This method will add up the scores for each criterion based on the requirements entered by the prospective internal reviewer participants, from these results it can be seen that the score obtained by each participant can be seen. This result will be taken into consideration by the committee or leadership in determining the internal reviewer at the Kuantan Singingi Islamic University